Racialized Architectural Space: A Critical Understanding of its Production, Perception and Evaluation. (19th April 2019) - Brown, Todd Levon
Abstract : Academic inquiry into the concept of space as racialized can be traced back to at least as far as the turn of the twentieth century with sociologist W. E. B. Dubois' promulgation of the "color-line" theory. More recently, numerous postmodern scholars from a variety of fields have elucidated the various ways in which physical space (i.e., the built environment), as a social product, embodies racialized ideologies exhibited and reproduced by segregation, economics and other social practices. The dialogue on race and space has primarily been limited to the urban scales of city, neighborhood, community and street. Socio-spatial research that centers around race rarely addresses this phenomenon at the scale of architecture – the individual building or a particular development. Such a failure to critically examine the role of the architectural product in the creation and reproduction of socio-spatial and socio-racial inequality yields the field of architectural practice exempt and blameless in its tangible contribution to the psychosocial and geospatial marginalization of communities of color, as in, for example, the case of gentrification. This paper attempts to illustrate the fact that architecture, like all of the built physical environment, is not ahistorical, apolitical – and certainly not race neutral – but, as a social product, is also understood clearly within these contexts, and its psychological and social impacts and outcomes must be examined with a racially critical lens, particularly in heterogeneous urban communities.